2023
DOI: 10.1039/d2lc00692h
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the elastic deformability of polydimethylsiloxane microfluidic channels for efficient intracellular delivery

Abstract: With the rapid development of microfluidic based cell therapeutics systems, the need arises for compact, modular, and microfluidics-compatible intracellular delivery platforms with small footprints and minimal operational requirements. Physical deformation...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
(54 reference statements)
0
5
0
Order By: Relevance
“…Compared with the control group, a certain degree of mechanical stimulation was able to align the length and angle of the cells ( n = 99 cells in each case), and it has been shown that explicit mechanical strain leads to the reorganization of the various cell types along the direction of the strain. Some scholars have shown that mechanical strain causes various cells to realign along the direction of the strain, and for cardiomyocytes, the alignment behavior is regulated by mechanotransduction resulting in “strain avoidance 44 , 45 ”. Through the above analysis, we can see a significant difference between the strains applied to our chip in the transverse and longitudinal directions, which is likely the reason for the rearrangement of the cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the control group, a certain degree of mechanical stimulation was able to align the length and angle of the cells ( n = 99 cells in each case), and it has been shown that explicit mechanical strain leads to the reorganization of the various cell types along the direction of the strain. Some scholars have shown that mechanical strain causes various cells to realign along the direction of the strain, and for cardiomyocytes, the alignment behavior is regulated by mechanotransduction resulting in “strain avoidance 44 , 45 ”. Through the above analysis, we can see a significant difference between the strains applied to our chip in the transverse and longitudinal directions, which is likely the reason for the rearrangement of the cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…The use of such large deformations is typically avoided in conventional engineering designs due to their nonlinear response of mechanical systems; however, as seen in the data here, an emergent feature of the dynamical motion-the frequency of pulsation-correlates almost linearly with the flow rates, thereby providing a robust route for flow sensing. Large-scale deformability of microfluidic components can provide further benefits (Xia et al 2021), such as the ability to dynamically adjust a constriction size for efficient cell transfection (Alhmoud et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…PDMS substrates, such as Sylgard molds, showcase high flexibility, rendering them ideal for creating microdevices and drug‐loaded microstructures. [ 73 ] PDMS substrates are characterized for their high elasticity and deformability, [ 120 ] which enable them to adapt to complex and intricate designs. [ 120 ] This distinctive flexibility is crucial in the precise fabrication of microdevices, ensuring that the final product accurately replicates the intended geometries.…”
Section: Substrates: Pioneering Precision Drug Delivery Through Versa...mentioning
confidence: 99%
“…[73] PDMS substrates are characterized for their high elasticity and deformability, [120] which enable them to adapt to complex and intricate designs. [120] This distinctive flexibility is crucial in the precise fabrication of microdevices, ensuring that the final product accurately replicates the intended geometries. Beyond their flexibility, PDMS substrates also possess excellent biocompatibility, [121,122] making them well-suited for applications involving interactions with biological tissues and fluids.…”
Section: Polydimethylsiloxanementioning
confidence: 99%